Deciphering the maize gene ZmGF14–3: implications for plant height based on co-expression networks - Wang, Hengsheng; Wei, Bo; Qi, Lulu; Chen, Yansong; Chen, Kelong; Liu, Dong; Su, Xu; Zhang, Yan; Li, Lingling (Frontiers in Plant Science, 2024)
The evolutionary analysis showed that the GF14 family was conserved, however, there was limited evidence linking GF14s to plant height. In our investigations, we discovered a co-expression relationship between ZmGF14s and functionally characterized genes linked to plant height. In the co-expression network, we identified ZmGF14-3, a gene expression exhibiting a positive correlation with plant height in three maize varieties, we postulated that this gene could be intimately linked to plant height development. Subsequently, we cloned ZmGF14-3 from the maize B73 inbred line and overexpressed it in Arabidopsis, resulting in markedly dwarfed transgenic phenotypes. Measurements of endogenous phytohormones disclosed a significant reduction in concentrations of Gibberellic Acid 7 (GA7) and Indole-3-Acetic Acid (IAA) in the overexpressed Arabidopsis, furthermore, qPCR results highlighted a pronounced decrease in the expression levels of plant height-related genes when compared to the wild type, therefore, it is plausible to posit that ZmGF14-3 plays a pivotal role in regulating the growth and development of maize through interactions with various phytohormone-related genes. Thus, delving into the potential interactions between ZmGF14-3 and these genes holds the promise of yielding valuable insights into the molecular mechanisms underpinning plant height development in maize.